Pengaruh Penambahan Kinesiotapping Pada Latihan Plyometrik Terhadap Peningkatan Power Lengan Pemain Tenis Lapangan - Crisvantikno, Rizky Meilynno; , Arif Pristianto, SSt.FT.,M.Fis (2016)
Background: Service is a technique that is used as an early starters tennis court, in its development service is a form of the first attack carried out so that the opponent difficult to repay resulting point. If the service is weak, the opposing player has the opportunity to take over the game and add the numbers in each attack, therefore the necessary power strong arm muscles to perform optimal service. Objective: This is to determine the effect of plyometrics exercises and the addition of Kinesio taping on plyometrics exercises to improve power arm tennis player. Methods: This research is a quasi experimental research design pre and post test two group design. A sample of 20 people. This study was divided into 2 groups each group divided 10 people. The first group was given a plyometric workout with 5 seconds long repetition is repeated 15 times to do three times a week for 4 weeks. The second group was given plyometric exercises with the addition of Kinesio taping technique in accordance with the facilitation of Origin insertion into the muscle with a strain of 25% and according to Kase techniques are not stretched to the end of the strip. Data analysis using paired samples t-test and independent sample t-test. Results: Test the effect in group I with plyometric exercises p value = 0.000 (p <0.005), while in group II with the addition of Kinesio taping on plyometric exercises p value = 0.000 (p <0.005). Different test results after treatment between groups I and II obtained value of p = 0.030. Conclusion: The addition of plyometric exercises and plyometric exercises, Kinesio taping on each influential in increasing muscle power arm tennis players, but the addition of Kinesio taping on plyometric exercises more influence than plyometric exercises.